Realidad aumentada como propuesta metodológica para la enseñanza en un entorno de aprendizaje escolar. - Eras Montaño, Eliza Josepht (2016)
Currently, traditional educational approaches have been severely affected due to the great advances in information and communication technologies. Because of this, more and more educational institutions that choose to innovate its archaic methodology, based on current technology, and so to establish an improvement in the learning process of students. Therefore, this project seeks to implement a technology that is at its peak, as is the Augmented Reality; within the school learning environment. Therefore, was designed, developed and evaluated a tool to serve as support for joining the concepts of a subject of Social Studies in an environment with augmented reality, and thus make it more dynamic and appealing to the interest of students. The project aims to students from fourth to sixth year of Basic General Education. The project will create a more pleasant and interesting class environment, breaking with the traditional class. The result was the creation of the "SolAR system" tool, which allows students to learn in an educational context without adding an additional level of learning difficulty. To learn about the level of acceptance of the tool, usability evaluations where carried out, they were applied during and after the production phase with end users. Methods of observation and evaluation of end user were used; allowing early detection and solve complications of interaction and information provided by the tool. Due to the good results obtained by the "SolAR system" in previous evaluations, we can say that is more than feasible to integrate the use of Augmented Reality, as study methodology, due to nice tools can be created for them. Consequently, this system represents a motivator for students who said they would work with the tool again.